Women administrators' conflicts and coping strategies in pursuing postgraduate degree / Bahiyah Mohd Shariff - Mohd Shariff, Bahiyah (2013)
Women are considered as backbone of a family. Women's roles has brought big impact in the perspective of social, economy and the country's well being. Women's contribution to the country's development cannot be denied as 36% of the work force in Malaysia comprises of women. This fact is supported by traits of women whom being focused, hardworking, attentive and responsible. Whilst the roles and responsibilities that women have to shoulder, some women are determine to further their studies to a higher level. It is intended to increase the qualification and quality of their education. However, the biggest challenge that these women face is to manage between carrier, education and family. How far can a woman be able to turn it to reality? This study is to investigate deeply on the use of coping strategies practiced by three women administrators who pursue their postgraduate degree despite their presence various commitments. Three women have been selected as the sample of the study. The researcher employs qualitative methods which involved questionnaires and sequel of interviews for in depth comprehension. The findings of the study revealed on coping strategies and styles being used. This paper also concludes by providing implications and recommendations for improvement of practices and future study.